CD28.OX40 co-stimulatory combination is associated with long in vivo persistence and high activity of CAR.CD30 T-cells - Marika Guercio; Domenico Orlando; Stefano Di Cecca; Matilde Sinibaldi; Iolanda Boffa; Simona Caruso; Zeinab Abbaszadeh; Antonio Camera; Biancamaria Cembrola; Katia Bovetti; Simona Manni; Ignazio Caruana; et al. (Haematologica, 2020)
The prognosis of many patients with chemotherapy-refractory or multiply relapsed CD30+ non-Hodgkin Lymphoma (NHL) or Hodgkin lymphoma (HL) still remains poor, and novel therapeutic approaches are warranted to address this unmet clinical need. In light of this consideration, we designed and pre-clinically validated a Chimeric Antigen Receptor (CAR) construct characterized by a novel anti-CD30 single-chain variable-fragment cassette, linked to CD3ζ by the signaling domains of two costimulatory molecules, namely either CD28.4-1BB or CD28.OX40. We found that CAR.CD30 T-cells exhibit remarkable cytolytic activity in vitro against HL and NHL cell lines, with sustained proliferation and pro-inflammatory cytokine production, even after multiple and sequential lymphoma cell challenges. CAR.CD30 T-cells also demonstrated anti-lymphoma activity in two in vivo xenograft immune-deficient mouse models of metastatic HL and NHL. We observed that administration of CAR.CD30 T-cells, incorporating the CD28.OX40 costimulatory domains and manufactured in the presence of IL7 and IL15, were associated with the best overall survival in the treated mice, along with the establishment of a long-term immunological memory, able to protect mice from further tumor re-challenge. Our data indicate that, in the context of in vivo systemic metastatic xenograft mouse models, the costimulatory machinery of CD28.OX40 is crucial for improving persistence, in vivo expansion and proliferation of CAR.CD30 T-cells upon tumor encounter. CD28.OX40 costimulatory combination is ultimately responsible for the antitumor efficacy of the approach, paving the way to translate this therapeutic strategy in patients with CD30+ HL and NHL.